Cardiovascular Responses Induced by Catalase Inhibitior into the Fourth Cerebral Ventricle is Changed in Wistar Rats Exposed to Sidestream Cigarette Smoke - Valenti, Vitor Engrácia [UNESP]; Abreu, Luiz Carlos de; Fonseca, Fernando L; Figueiredo, Jose-Luiz; Adami, Fernando; Ferreira, Celso (My University, 2013)
Objectives: This experimental study aimed to evaluate the effects of central catalase inhibition on cardiovascular responses in rats exposed to sidestream cigarette smoke (SSCS) for 3 weeks. Methodology: A total of 20 males Wistar rats (320–370g) were implanted with a stainless steel guide cannula into the fourth cerebral ventricle (4thV). Femoral artery and vein were cannulated for mean arterial pressure (MAP) and heart rate (HR) measurement and drug infusion, respectively. Rats were exposed to SSCS for three weeks, 180 minutes per day, 5 days/week [carbon monoxide (CO): 100–300 ppm)]. Baroreflex was tested with one pressor dose of phenylephrine (PHE, 8 μg/kg, bolus) and one depressor dose of sodium nitroprusside (SNP, 50 μg/kg, bolus). Cardiovascular responses were evaluated before and 15 minutes after 3-amino-1, 2, 4-triazole (ATZ, catalase inhibitor, 0.001g/100μL) injection into the 4th V. Results: Vehicle treatment into the 4th V did not change cardiovascular responses. Central catalase inhibition increased tachycardic peak, attenuated bradycardic peak and reduced HR range at 15 minutes, increased MAP at 5, 15 and 30 min and increased HR at 5 and 15 min. In rats exposed to SSCS, central ATZ increased basal MAP after 5 min and increased HR at 5, 15 and 30 minutes, respectively, and attenuated bradycardic peak at 15 minutes. Conclusion: This study suggests that brain oxidative stress caused by SSCS influences autonomic regulation of the cardiovascular system.